Surgical myocardial revascularization of patients with ischemic cardiomyopathy and severe left ventricular disfunction - Hovnanian, André L. (2010)
OBJECTIVE: To determine long-term survival, identify preoperative factors predictive of a favorable outcome, and assess functional improvement after coronary artery bypass grafting in patients with advanced left ventricular dysfunction. METHODS: Between 1995 and 2001, 244 patients who underwent coronary artery bypass grafting and had a preoperative left ventricular ejection fraction less than or equal to 35% were included. left ventricular ejection fraction was determined by uniplanar or biplanar ventriculography during left heart catheterization. Indication for surgery was predominance of tissue viability. Functional improvement was evaluated through echocardiography and gated scintigraphy at exercise/ rest. Survival was determined by Kaplan-Meier analysis. RESULTS: Mean left ventricular ejection fraction was 29±4% (ranged from 9% to 35%). An average of 3.01 coronary bypass grafts per patient were performed. In-hospital mortality was 3.7% (9 patients). The 4-year survival rate was 89.7%. Multivariate correlates of favorable short- and long-term outcome were preoperative New York Heart Association Funcional classification for congestive heart failure class I/II, lower PAsP, higher left ventricular ejection fraction and gated left ventricular ejection fraction Ex/Rest ratio >;5%. Left ventricular ejection fraction rise from 32±5% to 39±5%, p